Hepatoprotective Activity of Ethanol Extract of Mobe Leaves (Artocarpus lacucha Buch-Ham.) on Total Bilirubin, ALT, and AST Levels, and Macropathology of Liver in Rats Induced by Carbon Tetrachloride - Meiva Amelia Lubis; Aminah Dalimunthe; Panal Sitorus; Denny Satria; Arga Lubis (LPPM Universitas Harapan Bangsa, 2024)
This study evaluates the hepatoprotective effects of ethanol extract of mobe leaves (Artocarpus lacucha Buch-Ham.) in rats induced with carbon tetrachloride (CCl4). The objective was to determine the extract's efficacy in reducing liver damage markers, specifically total bilirubin, alanine aminotransferase (ALT), and aspartate aminotransferase (AST) levels, and to assess liver macropathology. The ethanol extract was prepared by maceration using 96% ethanol. Results showed that administering 400 mg/kg body weight (BW) of the extract significantly reduced total bilirubin, ALT, and AST levels in CCl4-induced rats. Additionally, liver macropathology observations indicated improved liver conditions in the treatment group. Phytochemical screening revealed bioactive compounds like flavonoids, alkaloids, tannins, saponins, triterpenoids, and glycosides, which are potential antioxidants and hepatoprotective agents. The significant contribution of this research is providing a scientific basis for using mobe leaf extract as a natural hepatoprotective agent, highlighting its potential for safe and effective herbal medicine. Further research and clinical trials are recommended to validate these findings and explore the extract's therapeutic applications.